Seminar Kesehatan Mental di Desa Pering: Pentingnya Mengenali Trauma dan Luka Batin - Pradevi, Putu Novira; Ni Made Novi Saraswati; Ni Kadek Sri Dianawati; I Wayan Oka Nugraha; Ni Kadek Astini; Ni Komang Tri Winayanti; I Made Subagia Antara; I Gede Ary Dwija Putra; Ni Kadek Yeli Maharani; Ni Kadek Vani Virmayanti; Ni Kadek Sania Muthia Putri; Luh Dewi Manik Mutiara Lestari; Ni Wayan Risca Herlyana; Putu Ayu Candra Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The Community Service Program (KKN) conducted in Pering Village by Group 15 of the Nusantara V Community Service Program (KKN Nusantara V) was not simply a stay at the designated village post and limited time to meeting with residents. However, through this Community Service Program, we were able to understand that in the social sphere, many things are actually kept hidden by individuals and are unable to communicate with those around them or those closest to them. If this continues, it can lead to something being kept hidden without relief, ultimately leading to trauma, depression, and emotional wounds. The Pering Village Head, in his remarks, stated that in Pering Village, several residents experience mental stress, depression, and even mental disorders. The Mental Health Seminar held in Pering Village aimed to increase public understanding of the importance of recognizing trauma and emotional wounds early. The event featured a psychologist who provided an in-depth explanation of the differences between emotional drama and psychological trauma, as well as how trauma can impact an individual's mental health. This seminar served as an educational platform for participants to increase self-awareness and encourage early detection of mental health issues so that appropriate and effective treatment can be provided. The seminar's findings demonstrate that increasing mental health literacy in the community is crucial for building emotionally and psychologically healthy communities. Therefore, this activity makes a significant contribution to reducing stigma and facilitating access to psychological support within the community. Keywords: Seminar, Mental Health, Psychology